Journalism and Big Data : the Nónio case - Lourenço, Vicente Maria Alexandre (2022)
As Clive Humby discribed in 2006, “Big Data is the new oil”, which is why in 2014 more than 91% of Fortune 1000 companies were investing in Big Data projects, based on the promise of higher returns. The goal of this study is to see if that is also happening with Portuguese media corporations by examining Big Data’s impact on content production and the business model of newspapers and news channels. Big Data is a term that simultaneously describes large pools of data as well as the computer techniques used to analyse those data sets. This investigation focuses on the NÓNIO project, a Big Data initiative developed by five of the largest media companies in Portugal: Cofina, Global Media, Grupo Renascença Multimédia, Impresa and Media Capital. This dissertation follows a qualitative approach. In order to gather insights on how the NÓNIO is shaping newsrooms, interviews are conducted with the people in charge of the project at each of the five media companies. Findings suggest that Big Data is having a small impact in content production, but a big one in the business model, as it is radically changing how media companies conduct advertising and how they attract and retain subscriptions.